2013 IEEE 15th International Conference on E-Health Networking, Applications and Services (Healthcom 2013) 2013
DOI: 10.1109/healthcom.2013.6720746
|View full text |Cite
|
Sign up to set email alerts
|

Real time falls prevention and detection with biofeedback monitoring solution for mobile environments

Abstract: With the elderly population growing around the world, falls increase the risk progressively with age. Those falls can origin injuries that may cause a great dependence and debilitation to the elderly, and even death in extreme cases. This paper reviews the related literature about this topic and introduces a mobile solution for falls prevention, detection, and biofeedback monitoring. The falls prevention system uses collected data from sensors in order to control and advice the patient or even to give instruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Pre-FPIs aim to overcome intrinsic fall risk factors such as vision, balance, muscle strength and cognitive decline [ 41 , 42 ]. With regard to intrinsic fall risk factors, functional ability was the main focus of a number of studies [ 43 , 44 , 45 ]. In these studies, various technologies were used to proactively mitigate observed deficits in functional ability.…”
Section: Fall Prevention Systemsmentioning
confidence: 99%
“…Pre-FPIs aim to overcome intrinsic fall risk factors such as vision, balance, muscle strength and cognitive decline [ 41 , 42 ]. With regard to intrinsic fall risk factors, functional ability was the main focus of a number of studies [ 43 , 44 , 45 ]. In these studies, various technologies were used to proactively mitigate observed deficits in functional ability.…”
Section: Fall Prevention Systemsmentioning
confidence: 99%
“…In some cases, the smartphone operates under a more ambitious monitoring scheme not only intended to detect falls but also other biosignals. For example, the systems presented by Horta et al in [52,53] integrate a smartphone and a set of Bluetooth-enabled medical sensors aimed at providing biofeedback monitoring. In other cases, the additional sensors are incorporated to the FDS in order to help the personal device with the detection decision.…”
Section: Consumption In Hybrid Fall Detection Architectures (Combininmentioning
confidence: 99%
“…Typically, ECG is used to assess the electrical and muscular operations of the heart but ECG sensing can Advances in Human-Computer Interaction 3 also determine abnormalities that might lead to a fall [23,24].…”
Section: Classification Of Fall Factorsmentioning
confidence: 99%